Скалярный электрический и векторный магнитный потенциалы в теории электромагнитного поля - Глухенький, А.И.; Гориславец, Ю.М. (Технічна електродинаміка, 2012)
The special features in formation of Maxwell's electrodynamics and classic theory of electromagnetic field are examined. The advantages that follow from consideration of scalar electric and vector magnetic potentials as physical quantities are demonstrated.